Human dental pulp stem cell responses to different dental pulp capping materials - Manaspon, Chawan (BMC Oral Health, 2021)
BACKGROUND: Direct pulp capping is a vital pulp therapy for a pin-point dental pulp exposure. Applying a pulp capping material leads to the formation of a dentin bridge and protects pulp vitality. The aim of this study was to compare the effects of four dental materials, DyCal(®), ProRoot(®) MTA, Biodentine™, and TheraCal™ LC in vitro. METHODS: Human dental pulp stem cells (hDPs) were isolated and characterized. Extraction medium was prepared from the different pulp capping materials. The hDP cytotoxicity, proliferation, and migration were examined. The odonto/osteogenic differentiation was determined by alkaline phosphatase, Von Kossa, and alizarin red s staining. Osteogenic marker gene expression was evaluated using real-time polymerase chain reaction. RESULTS: ProRoot(®) MTA and Biodentine™ generated less cytotoxicity than DyCal(®) and TheraCal™ LC, which were highly toxic. The hDPs proliferated when cultured with the ProRoot(®) MTA and Biodentine™ extraction media. The ProRoot(®) MTA and Biodentine™ extraction medium induced greater cell attachment and spreading. Moreover, the hDPs cultured in the ProRoot(®) MTA or Biodentine™ extraction medium migrated in a similar manner to those in serum-free medium, while a marked reduction in cell migration was observed in the cells cultured in DyCal(®) and TheraCal™ LC extraction media. Improved mineralization was detected in hDPs maintained in ProRoot(®) MTA or Biodentine™ extraction medium compared with those in serum-free medium. CONCLUSION: This study demonstrates the favorable in vitro biocompatibility and bioactive properties of ProRoot(®) MTA and Biodentine™ on hDPs, suggesting their superior regenerative potential compared with DyCal(®) and TheraCal™. SUPPLEMENTARY INFORMATION: The online version contains supplementary material available at 10.1186/s12903-021-01544-w.